Pengembangan bahan ajar ekonomi berbasis ilustrasi gambar dalam tampilan majalah untuk meningkatkan minat belajar siswa kelas x ma nw pengadang Tahun ajaran 2017/2018 - Saparwadi sapar; Siti Rohayu (FAKULTAS TARBIYAH, 2021)
The objectives of this research are: (1) to develop teaching materials based on the illustration of images in magazine displays to increase students' learning interest in class X MA NW Pengadang; (2) to know the feasibility of illustration-based illustrations of images in magazine display to increase student belajar interest in class X MA NW Pengadang; (3) to find out teacher's response and student's response to the development of illustration-based instructional materials in magazine appearances on economic subjects in class X MA NW Pengadang; (4) to know the increase of student's interest to the instruction of economic resource-based illustration of the image in magazine display. This type of research is Research and Development (R n D) research using Borg & Gall development model. The subjects of the study were the students of class X MA NW Pengadang consisting of 2 trials, the small group trial amounted to 9 students, and the large group trial amounted to 30 students. The main instrument in this research is the illustration-based teaching materials in magazine displays to improve students' learning interests. Data collection techniques used observation techniques, interviews, and questionnaires. The technique of data analysis uses the Likert scale which is then changed to a percentage number and draw conclusions and descriptive statistics. The result of the research shows the following: (1) The result of the feasibility test of the expert team which includes media experts and material experts obtained by material validation is equal to 76% with valid category, and display validation is 91% with very good category / feasible (valid) without needing to revise. (2) the result of the scoring of teachers obtained a score of 73 with a percentage of 82% in the category of very good (valid). (3) In the small group trial obtained an average score of 10.4 with a percentage of 94.94% in the very good category. (4) While in the large group trial obtained an average score of 9.6 with 96.66% percentage in the very good category. (5) measurement results increase student learning interest in obtaining an average percentage of 75.75% in increasing categories. The overall results of the study show the economic resource-based illustrations of images in the magazine display to improve the learning of the soul on the material money worthy of use in economic learning